HIV-related knowledge and stigma towards people living with hiv among community in Tawau, Sabah - Sudarman, Abdul Halim (Universiti Sains Malaysia, 2024)
Human Immunodeficiency Virus (HIV) is a major global health issue and of the most dreaded pandemic that damages or inhibits the human immune system when it infects a person. HIV stigma is negative belief, feelings and attitudes towards people living with HIV, groups associated with people living with HIV and other key populations at higher risk of HIV infection, such as people who inject drugs, sex workers, men who have sex with men and transgender people. This study is to determine the level of knowledge and the level stigma among community in Tawau, Sabah. A study among community (N=190) was done in community at Tawau, Sabah. This study was conducted using self-administered questionnaire. Data were analysed with descriptive statistics and Pearson Correlation test by using Statistical Package Social Science (SPSS) version 27.0 software. The mean for level of knowledge in this study is 11.27 (SD 3.93) and the mean for level of stigma in this study is 9.96 (SD 2.50). Most of the participants in this study (N=118, 54.9%) have moderate level of knowledge and (N=121, 56.3%) have moderate stigma. Pearson Correlation test revealed that there is statistically significant correlate between levels of knowledge and stigma towards PLHIV (p<0.05). In summary, it should be possible to decrease negative stereotypes about HIV-positive individuals by reducing stigma and increasing public understanding of HIV-related concerns.